All Days 2001
DOI: 10.2118/67753-ms
|View full text |Cite
|
Sign up to set email alerts
|

Coiled Tubing Seismic While Drilling

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe efficient exploitation of hydrocarbon resources is strongly dependent on the drillers' ability to position wells accurately. This is particularly challenging for smaller targets and on long reach or horizontal wells. Conventional wireline VSP's can provide valuable assistance but such operations require either the drill string to be removed from the hole or the pumping of the geophone tool through the drill string. Both of these methods add time to the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, it has been found that the technique using the bit as a source is generally ineffective in soft sediments, horizontal wells, and while drilling with polycrystalline diamond compact (PDC) bits. 3 The alternative to SWD is intermediate wireline checkshot or vertical seismic profile (VSP) surveys, which are typically run to reduce the uncertainty in putting the drill bit on seismic images and sometimes to provide a velocity model for seismic reprocessing. Being able to make this VSP or check-shot survey while drilling can significantly reduce costs by eliminating wireline rig time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been found that the technique using the bit as a source is generally ineffective in soft sediments, horizontal wells, and while drilling with polycrystalline diamond compact (PDC) bits. 3 The alternative to SWD is intermediate wireline checkshot or vertical seismic profile (VSP) surveys, which are typically run to reduce the uncertainty in putting the drill bit on seismic images and sometimes to provide a velocity model for seismic reprocessing. Being able to make this VSP or check-shot survey while drilling can significantly reduce costs by eliminating wireline rig time.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic source for the field tests consisted of three 150-in 3. air guns mounted on a triangular frame.…”
mentioning
confidence: 99%